Research Progress on the Application of Elemental Fingerprinting in Tea Origin Traceability and the Influencing Factors Thereof - LI Yanlong, QIAN Lili, CHEN Mingming, SONG Yan, LIU Yi, WANG Yongsheng, LIU Hongyan (Shipin Kexue)
Tea origin traceability is an important means to ensure the quality and safety of tea. Currently, China’s tea traceability system is under rapid development. Incidents of tea origin and product counterfeiting are not uncommon. Fortunately, the application of elemental fingerprinting technology provides a new solution for tracing the origin of tea. This article summarizes the progress on elemental fingerprinting in tracing the origin of tea and influencing factors thereof, introduces the domestic and international progress that has been made over the past decade in the application of stable isotopes and mineral elemental fingerprinting in tea origin tracing, discusses the impacts of geographical environment, tea tree varieties and processing techniques on tea elemental fingerprints, and proposes future research directions for tea traceability technology, aiming to provide references for achieving more accurate traceability of tea origin.